Skeletal Muscle Interleukin-6 Contributes to the Innate Immune Response in Septic Mice. Issue 5 (May 2021) - Laitano, Orlando; Robinson, Gerard P.; Garcia, Christian K.; Mattingly, Alex J.; Sheikh, Laila H.; Murray, Kevin O.; Iwaniec, John D.; Alzahrani, Jamal; Morse, Deborah; Hidalgo, Juan; Clanton, Thomas L.
Abstract : ABSTRACT: Interleukin-6 (IL-6) is a major cytokine released by skeletal muscle. Although IL-6 plays complex but well-known roles in host defense, the specific contribution of skeletal muscle IL-6 to innate immunity remains unknown. We tested its functional relevance by exposing inducible skeletal muscle IL-6 knockdown (skmIL-6KD) mice to a cecal slurry model of polymicrobial peritonitis and compared responses to strain-matched controls and skeletal muscle Cre -matched controls at 3, 6, and 12 h postinfection. In both sexes, skmIL-6KD mice at 6 h of infection exhibited marked changes to leukocyte trafficking in the peritoneum, characterized by ∼1.75-fold elevation in %neutrophils, a ∼3-fold reduction in %lymphocytes and a ∼2 to 3-fold reduction in %basophils. A similar pattern was seen at 12 h. No changes were observed in plasma leukocyte counts. Circulating cytokines in female skmIL-6KD mice at 6 h consistently showed modest reductions in IL-6, but marked reductions in a broad range of both pro- and anti-inflammatory cytokines, e.g., TNFα and IL-10. In both sexes at 12 h, a generalized suppression of plasma cytokines was also seen after the effects of Cre -induction with raloxifene were addressed. There were no significant effects of skmIL-6KD on mortality in either sex. Collectively, our results are consistent with skmIL-6 playing an important and previously unrecognized role in immune cell trafficking and cytokine regulation during septic shock. Abstract : Supplemental Digital Content is available in the text